2022
DOI: 10.1002/adma.202208600
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow‐Power Vertical Transistors for Multilevel Decoding Modes

Abstract: addressing probabilistic, and unstructured problems, thus is anticipated to solve the von Neumann bottleneck and become the mainstay of contemporary computing systems. [1,2] Synapses serve a crucial function in signal transmission in the biological neural system. [3] They transmit signals through neurotransmitters in a manner similar to that of field-effect transistors, where source-drain current changing in response to changes in gate voltage. In addition, organic materials are solutionprocessable, [4][5][6][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…2g, which indicates a lower energy consumption of this work, even lower than that of the biological system (10 fJ per synaptic event). 25,[43][44][45][46][47][48][49][50][51][52][53][54] The result indicated that the device in this work has great potential in simulating the behaviors and energy consumption of human brain synapses.…”
Section: Journal Of Materials Chemistry C Papermentioning
confidence: 99%
“…2g, which indicates a lower energy consumption of this work, even lower than that of the biological system (10 fJ per synaptic event). 25,[43][44][45][46][47][48][49][50][51][52][53][54] The result indicated that the device in this work has great potential in simulating the behaviors and energy consumption of human brain synapses.…”
Section: Journal Of Materials Chemistry C Papermentioning
confidence: 99%
“…A summary for the synaptic vertical transistors based on different materials. [66,94,95,104,[107][108][109][110][111] Reproduced with permission. [66] Copyright 2021, John Wiley and Sons.…”
Section: Basic Principles Of Biological Nervous System and Neuromorph...mentioning
confidence: 99%
“…To overcome this drawback, Chen et al constructed a high‐performance vertical transistor with an ultralow power consumption using MXene (transition metal carbides/nitrides) to realize the multilevel information decoding strategies. [ 104 ] Figure a depicts the preparing process of vertical MXene‐DPA transistor. The information decoding ability of VOFET is explored after evaluating its electrical and optoelectric performances.…”
Section: Vertical Transistors and Their Bionic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations